Insolvency and Enforcement Reforms in Italy - Garrido, Jose (IMF Working Papers; Working Paper ;, 2016)
Italian banks are burdened with high levels of nonperforming loans, the cleanup of which depends in important part on the efficiency of insolvency and enforcement processes. Traditionally, these processes in Italy have taken very long, hampering the timely cleanup of balance sheets. In response, the authorities have legislated a number of measures. This paper explores the recent insolvency and enforcement reforms and the remaining challenges. These reforms introduce important positive changes that are expected to yield full benefits over the medium to long term. The efficacy of the reforms, including to deal with the current stock of high nonperforming loans, can be enhanced by introducing effective out-of-court enforcement mechanisms, supplemented by a more intensive use of informal and hybrid debt-restructuring solutions. Moreover, there is an urgent need to rationalize the system, which over the years has become very complex and intricate.